2014
DOI: 10.1080/14789949.2014.981563
|View full text |Cite
|
Sign up to set email alerts
|

Interventions with women offenders: a systematic review and meta-analysis of mental health gain

Abstract: Currently, a conjunction of policy, legislative change in health and social care and the criminal justice system, combined with funding for innovative services make it opportune to assess the evidence base for interventions with women offenders. Women offenders have a distinctive criminological, health and social profile and a gender specific approach to their difficulties is advocated. This systematic review and meta-analysis focus on mental health gain in adult women offenders in forensic health settings, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…Bartlett, Jhanjib, Whitec, & Harty, 2014;Blanchette & Brown, 2006;Covington & Bloom, 2006;Heilbrun et al, 2008;Long, Fulton, & Hollin, 2008). In general, these treatment models stress the importance of using gender-sensitive risk assessment and addressing issues such as trauma, (sexual) abuse, and the role of social relations and disruptions in these relations Downloaded by [Orta Dogu Teknik Universitesi] at 09:54 30 December 2015 during treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Bartlett, Jhanjib, Whitec, & Harty, 2014;Blanchette & Brown, 2006;Covington & Bloom, 2006;Heilbrun et al, 2008;Long, Fulton, & Hollin, 2008). In general, these treatment models stress the importance of using gender-sensitive risk assessment and addressing issues such as trauma, (sexual) abuse, and the role of social relations and disruptions in these relations Downloaded by [Orta Dogu Teknik Universitesi] at 09:54 30 December 2015 during treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Women's psychosocial problems and needs are well documented in the correctional literature from Scandinavia (Amundsen, 2011;Cramer, 2014;Lindberg, 2005;Mathiassen, 2011;Yourstone et al, 2010), and other countries in Europe and outside Europe (Bartlett et al, 2014;Black et al, 2013;Chen, 2010;Covington, 2008, Leschied, 2011Sacks et al, 2012;Sapouna et al, 2011;Zaplin, 2008;Zlotnick et al, 2008Zlotnick et al, , 2009Van Wormer, 2010). Recently, a Norwegian study demonstrated that one out of four women reported major or moderate depression (Cramer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The need to maintain the changes and provide continuity of care upon release from prison and when the women resettle in the community, is evident. When planning programs and interventions for women, attention must be paid to follow-up periods (Bartlett et al, 2014).…”
Section: Social Contextmentioning
confidence: 99%
See 2 more Smart Citations